Heidegger ai margini. Antropologia e trasgressione dello spazio urbano: un caso studio - Pozzi, Giacomo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
The Programa Especial de Realojamento (PER) offers the opportunity to the municipalities situated in Lisbon and Porto metropolitan areas of succeeding in eliminating clandestine neighborhoods and providing the reallocation of the residents in social houses. The decree contextualizes the housing problem as «a still open plague in our social fabric».The current process implementation, more than twenty-year far from the original formulation, has produced complex adaptation, resistance and fighting dynamics. Through the analyses of an ethnographic case study, the author problematizes the implementation of this governance program, focusing on the consequent systematic demolition of informal settlements in the Lisbon periphery under the aegis of the urban renewal doctrine.